Long term follow-up results of enucleation as the definitive treatment for melanocytic neuroectodermal tumour of infancy and a review on its treatment - Tsering Dekyi; Kamalpreet Kaur; Ongkila Bhutia; Ajoy Roychoudhury; Deepika Mishra; Vivek Nayyar (Elsevier, 2023)
Introduction: Melanotic Neuroectodermal tumour of Infancy (MNTI) is a rare entity of pigmented neoplasms of head and neck region. It predominantly occurs within the first year of life. The authors present enucleation as the definitive surgical treatment, with reference to the five departmental cases of MNTI with no recurrence at 5years and 1year of follow-up of other 4 cases. Case presentation: Five cases of MNTI (age group of 2.5months-7 months) presented to our department as a large bluish-brown non tender swelling protruding into the oral cavity. Radiologic imaging revealed a well-circumscribed solid-cystic enhancing lesion causing elevation of orbit and nasal obliteration in maxillary region and causing buccolingual expansion in mandible. The tumor was enucleated without any bony margin. Histopathological and immunohistochemical evaluation (EMA, Pan Cytokeratin, HMB45, S100, p53, ki67) were done. Patients were followed up at regular intervals and had no recurrence at mean 3years follow-up. A detailed mention of surgical pearls, differential diagnosis and a brief literature review are also done. Conclusion: MNTI is a pigmented neoplasm that occurs in infants and in head and neck region mostly involves the upper alveolus and maxilla, followed by skull and mandible. Incisional biopsy is needed to confirm the tumour and rule out other malignant round cell tumours. Enucleation of the lesion is necessary without the need for any extra bony margin removal. Close long term follow up is necessary. Conservative surgical approach is usually the best first choice for MNTI treatment.